AS/RS Technology Selection Using Interval-Valued Pythagorean Fuzzy WASPAS - Boltürk, Eda; Kahraman, Cengiz (Springer International Publishing, 2019)
Pythagorean fuzzy sets (PFSs) have been introduced by Yager [1] and they assign membership and non-membership in a wider area more than intuitionistic fuzzy sets. In this paper, we employ Pythagorean fuzzy sets for developing of interval-valued Pythagorean fuzzy sets. Weighted Aggregated Sum Product Assessment (WASPAS) is a multi-criteria decision making method and it is a combination method consist of the methods of simple additive weighting (SAW) and weighted product method (WPM). Automated Storage and Retrieval Systems are computer controlled systems for placing packs in storages and warehouses. The proposed method is applied to an Automated Storage and Retrieval Systems technology selection problem.